Nictaba Homologs from Arabidopsis thaliana Are Involved in Plant Stress Responses - Eggermont, Lore; Stefanowicz, Karolina; Van Damme, Els J. M. (Frontiers in Plant Science, 2018)
Plants are constantly exposed to a wide range of environmental stresses, but evolved complicated adaptive and defense mechanisms which allow them to survive in unfavorable conditions. These mechanisms protect and defend plants by using different immune receptors located either at the cell surface or in the cytoplasmic compartment. Lectins or carbohydrate binding proteins are widespread in the plant kingdom and constitute an important part of these immune receptors. In the past years, lectin research has focused on the stress inducible lectins. The Nicotiana tabacum agglutinin, abbreviated as Nictaba, served as a model for one family of stress-related lectins. Here we focus on three non-chimeric Nictaba homologs from Arabidopsis thaliana, referred to as AN3, AN4 and AN5. Confocal microscopy of ArathNictaba EGFP fusion constructs transiently expressed in Nicotiana benthamiana or stably expressed in A. thaliana yielded fluorescence for AN4 and AN5 in the nucleus and the cytoplasm of the plant cell, while fluorescence for AN3 was only detected in the cytoplasm. RT-qPCR analysis revealed low expression for all three ArathNictabas in different tissues throughout plant development. Stress application altered the expression levels, but all three ArathNictabas showed a different expression pattern. Pseudomonas syringae infection experiments with AN4 and AN5 overexpression lines demonstrated a significantly higher tolerance of several transgenic lines to P. syringae compared to wild type plants. Finally, AN4 was shown to interact with two enzymes involved in plant defense, namely TGG1 and BGLU23. Taken together, our data suggest that the ArathNictabas represent stress-regulated proteins with a possible role in plant stress responses. On the long term this research can contribute to the development of more stress resistant plants.